Pancreas volume and fat deposition in type ii diabetes mellitus - Ramanaidu, Anusha (2022)
Background: Diabetes mellitus is a metabolic disease associated with a defect of β cell function that causes insulin resistance characterised by hyperglycemia. In the diabetes mellitus population, the reduction of pancreatic volume and an increase in the pancreas attenuation cause uncontrolled sugar in patients. In patients with type II diabetes mellitus, there is a strong association between pancreas volume and pancreatic attenuation. Many studies conducted in Europe and other Asian countries showed diabetes mellitus has an association with reduced pancreas volume and an increase in pancreas attenuation in diabetes mellitus population. The aim of this study is to establish a significant reduction in pancreatic volume and an increase in the pancreatic attenuation in type II diabetes mellitus, in comparison with the non-diabetes mellitus population, based on the assessment using computed tomography (CT) among the Malaysian population. In Malaysia, no study has been conducted to evaluate pancreas changes among type II diabetes mellitus patients. The various external factors such as lifestyle, diet, and body habitus influence these pancreatic changes. Another objective is to see metabolic factors’ association with type II diabetes mellitus patients. Methods: A prospective cross-sectional study was conducted at Hospital University Sains Malaysia (HUSM), Kota Bharu, Kelantan, Malaysia involving 74 subjects who underwent elective CT scan abdomen/pelvis for various other indications were enrolled in this study. Patients were classified into type II diabetes mellitus and non-diabetes mellitus. Among these subjects 39 were non-diabetic and 35 were diabetic. The age of these subjects ranged from 35 to 70 years old with a mean age of 56 years old. There were 34 female and 30 male subjects respectively. A single observer was used to measure the pancreatic volume and pancreas attenuation. CT abdomen images were analysed and measured at the workstation using the Picture Archive and Communication system (PACS). Pancreas volume were measured by using formula (APtail + APbody)/2 x L(body&tail) X CCbody + (APhead/2) x 3.14 x CC head. The CC diameter is calculated by multiplication of the number of sections of a particular part of the pancreas according to the slice thickness. The pancreas attenuation was obtained using ROI and measuring Hounsfield units between the pancreas and spleen, then using the formula to measure pancreas attenuation (HU p–s). The volume of pancreas and pancreas attenuation were then compared between type II diabetes mellitus and non-diabetes mellitus using an independent t-test. The covariates were analysed by using ANCOVA.Results The type II diabetic mellitus patients had a significantly smaller mean pancreas volume with a mean difference of 10.18cm3 (95% CI = 2.16, 18.20). The mean average of pancreatic volume with a standard deviation (SD) of 64.82cmᶾ in Type II Diabetes Mellitus and 75.00cmᶾ in Non-Diabetes Mellitus subjects. The pancreas volume is categorised into the normal or reduced size, in diabetic patients with a higher proportion of reduced pancreas (p = 0.003). There was no significant difference in normal pancreas attenuation between the type II diabetes mellitus and non-diabetes mellitus patients. The mean average of pancreatic attenuation HU (pancreas – spleen) has a standard deviation (SD) of – 4.7 and the standard deviation (SD) of type II diabetes mellitus and non-diabetes mellitus subjects was– 5.74 and – 3.86 respectively. The covariates age, HbA1c, and fasting blood sugar level significantly correlate with pancreatic volume in type II diabetes mellitus, in which all these variables had a moderate inverted correlation. Only body mass index (BMI) has a significant correlation with an increase in normal pancreatic attenuation with a moderate inverted correlation. Conclusion: Type II diabetes mellitus observed a significant reduction in pancreatic volume. For pancreatic volume, metabolic factors such as age, HbA1c, and fasting blood sugar have a moderate inverted correlation. However, the normal pancreatic attenuation doesn’t show a significant correlation between type II diabetes mellitus and the non- diabetes Mellitus population. In type II diabetes mellitus only, BMI shows a significant correlation with an increase in pancreas attenuation